Bacterial and Fungal Gut Community Dynamics Over the First 5 Years of Life in Predominantly Rural Communities in Ghana - Amenyogbe, Nelly; Adu-Gyasi, Dennis; Enuameh, Yeetey; Asante, Kwaku Poku; Konadu, Dennis Gyasi; Kaali, Seyram; Dosoo, David; Panigrahi, Pinaki; Kollmann, Tobias R.; Mohn, William W.; Owusu-Agyei, Seth (Frontiers in Microbiology, 2021)
Background: Bacterial and fungal microbiotas are increasingly recognized as important in health and disease starting early in life. However, microbiota composition has not yet been investigated in most rural, low-resource settings, and in such settings, bacterial and fungal microbiotas have not been compared. Thus, we applied 16S and ITS2 amplicon sequencing, respectively, to investigate bacterial and fungal fecal microbiotas in rural Ghanaian children cross-sectionally from birth to 5 years of age. Corresponding maternal fecal and breastmilk microbiotas were additionally investigated. Results: While bacterial communities differed systematically across the age spectrum in composition and diversity, the same was not observed for the fungal microbiota. We also identified a novel and dramatic change in the maternal postpartum microbiota. This change included much higher abundance of E. coli and much lower abundance of Prevotella in the first versus fourth week postpartum. While infants shared more bacterial taxa with their mother’s stool and breastmilk than with those of unrelated mothers, there were far fewer shared fungal taxa. Conclusion: Given the known ability of commensal fungi to influence host health, the distinct pattern of their acquisition likely has important health consequences. Similarly, the dynamics of mothers’ bacterial microbiotas around the time of birth may have important consequences for their children’s health. Both topics require further study.